Estimating cleat characteristics in reservoir simulation models of coal seam gas reservoirs using welltest analysis - Bahrami, N.; Byfield, R.; Hossain, Mofazzal; Chitgar, A.; Wong, J. (2015)
Copyright 2015 Society of Petroleum Engineers.Coal Seam Gas reservoirs are naturally fractured and the flow of fluid throughout the coal occurs by diffusion through the coal matrix and then via the cleats (network of fractures) towards the wellbore. Effective permeability of the cleats and Langmuir isotherm parameters of the matrix coal blocks are the key parameters in determining the economic viability of producing from a CSG reservoir. Welltest analysis in CSG wells is more complicated than conventional reservoirs due to the stress sensitive permeability of the cleats and the great heterogeneity of coal. Fluid pressure inside the cleats initially controls the stress sensitive permeability. During production and at the reduced pressure near the wellbore region, the cleats have smaller aperture and less permeability than the cleats away from the wellbore due to the in-situ stresses. Conversely during injection, the cleats near the wellbore have higher permeability than the cleats away from the wellbore. The common well test analysis methods normally provide undefined values of average permeability and skin factor, rather than addressing the effective permeability of the cleats. This study presents how to interpret the skin factor in a CSG welltest, and also proposes a methodology using integration of welltest analysis and image log data processing results for estimation of cleat characteristics in CSG reservoirs to be input in a dual porosity CSG reservoir simulation model.